Take one can : 80 delicious meals from the cupboard - Milne, Lola (Kyle Books, 2020)
Our kitchen cupboards are full of cans - tomatoes, chickpeas, tuna, kidney beans, sardines, sweetcorn, even figs - that often are used as an addition to a recipe but never the main ingredient. This books is a celebration of canned ingredients, offering 80 recipes that take one can and make it the focus of the meal.